1998
DOI: 10.1046/j.1365-2915.1998.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Thanaka (Limonia acidissima) and deet (di‐methyl benzamide) mixture as a mosquito repellent for use by Karen women

Abstract: The prevention and treatment of drug-resistant malaria is becoming increasingly difficult. On the Thai-Myanmar border multi-drug resistant strains of falciparum malaria are increasing and, because the malaria vector Anopheles bite outdoors during early evening, insecticide house-spraying or impregnated bednets provide only limited protection. Therefore, the protective efficacy of repellent formulations containing di-methyl benzamide (deet) and permethrin against local vectors was estimated, when applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Field trials in Thailand and Malaysia show di-ethyl- N,N- toluamide (DEET) concentrations of 15–20% decrease mosquito biting by over 83% [8]–[10]. However few trials have been able to demonstrate an effect on malaria transmission by the use of insect repellent.…”
Section: Introductionmentioning
confidence: 99%
“…Field trials in Thailand and Malaysia show di-ethyl- N,N- toluamide (DEET) concentrations of 15–20% decrease mosquito biting by over 83% [8]–[10]. However few trials have been able to demonstrate an effect on malaria transmission by the use of insect repellent.…”
Section: Introductionmentioning
confidence: 99%
“…34,127,145,146 Review dawn, when they may already be awake and active, potentially restricting the protective eff ect of treated nets. 147 Mosquito repellents with N,N-diethyl-metatoluamide (DEET) are safe in pregnancy, 148,149 can reduce exposure to insect bites, 148 and resulted in a nonsignifi cant reduction in the incidence of P falciparum infection in pregnant women in one possibly underpowered study. 142 Mefl oquine chemoprophylaxis gave 86% protection against P falciparum and complete protection against P vivax infection in a double-blind, placebo-controlled study 49 at the Thai-Burmese border when mefl oquine was still fully eff ective.…”
Section: Preventionmentioning
confidence: 99%
“…In addition to this, a community-randomized trial with DEET in South America showed no effect on malaria incidence rates (Kroeger et al 1997), while a recent outbreak of malaria in a village in South Africa was controlled by use of DEET as repellent among the affected population (Durrheim and Govere 2002). Another study in ThaiMyanmar border with multidrug resistant strains of P. falciparum malaria, use of a mixture of a root paste made from pulp of the wood apple tree "Thanaka" (Limonia acidissima,) and DEET by Karen pregnant women found to reduce mosquito bites (Lindsay et al 1998). McGready et al (2001a reported lower accumulation of DEET in cord blood (8%, n=50, 95% confidence interval 2.6-18.2) applied regularly to Karen pregnant women during the second and third trimesters of pregnancy without adverse effects on survival, growth, and development at birth and up to 1 year, indicating considerable safety.…”
Section: Personal Protection Methodsmentioning
confidence: 94%